KNOWLEDGE OF NEONATAL SCREENING AND ITS OPERATIONALIZATION - Ivanete da Silva Santiago Strefling; Xênia Martins Monfrim; Wilson Danilo Lunardi Filho; Karen Knopp de Carvalho; Ana Lucia Soares de Azevedo (Universidade Federal do Paraná, 2014)
This exploratory-descriptive study, with a qualitative approach, aimed to describe nurses' knowledge relating to neonatal screening and its operationalization. The study participants were 13 nurses working in seven Family Health Strategy Centers in a city in the south of the State of Rio Grande do Sul, in May - July 2010. The data were collected in semi-structured interviews and were analysed using the technique of the Discourse of the Collective Subject. The interviewees showed knowledge concerning the neonatal screening test regarding its aim, the ideal period for blood collection, the collection technique, the diseases tracked, and which of them the State is equipped to diagnose. During the study, the importance was emphasized of the nursing professional continuously seeking technical-scientific training. Concomitantly, the need was perceived for public managers to provide more training opportunities to the health professionals.